Znaczenie zaufania i kooperacji w wymiarach lokalnych widziane z perspektywy 25 lat samorządności w Polsce - Konopka, Dorota (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2016)
The article attempts to examine the progress that has been made in the area of self-government over the last quarter century in Poland. Not only has the chaos in the institutional process in this period affected the overall low level of citizens’ trust in democratic institutions, but it also led to absence of effective cooperation between them. The author indicates two methods of both increasing public trust in the institution and increasing effectiveness of cooperation between institutions themselves, i.e. systematic changes in the self-government and glocalization of public trust.